Prediction of Temperatures During Friction Stir Welding of AA6061 Aluminium Alloy Using Hyperworks - Yatapu, Yaswanth Rao (Asian Research Publishing Network (ARPN), 2016)
This document contains the formatting information for the papers presented at the International conference on “Engineering Technology International Conference”. The conference held at (Bali, Indonesia) during August 10-11, 2015. The microstructure and mechanical properties of the material to be welded mainly depends on the temperature during welding. The difficulty in measuring these temperatures during friction stir welding, pose a serious concern to researchers, practicing engineers and technicians. Hence, there is a necessity for searching alternate solutions. In the present research, a simulation model has been developed by using hyper works software to estimate the temperatures and flow stress. The modeling of Friction Stir Welded AA6061 alloy has been carried out by three dimensional nonlinear FEA model, the temperatures are evaluated. During the welding process the peak temperatures and flow stresses are presented around the rotating tool pin, and plates are found to be 615 0 C and 450 0 C.